On the existence, uniqueness, and nonexistence of solutions of one boundary-value problem for a semilinear hyperbolic equation - Midodashvili, B.; Kharibegashvili, S. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.956.35 We consider a boundary-value problem for a semilinear hyperbolic equation with iterated multidimensional wave operator in the principal part. The theorems on existence, uniqueness, and nonexistence of solutions of this problem are established.